Informatics in control, automation and robotics : 11th International Conference, ICINCO 2014, Vienna, Austria, September 2-4, 2014 revised selected papers /: 11th International Conference, ICINCO 2014, Vienna, Austria, September 2-4, 2014 revised selected papers. (2015) - Unknown
No abstract available